2022
DOI: 10.1073/pnas.2119599119
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac sympathetic-vagal activity initiates a functional brain–body response to emotional arousal

Abstract: Significance We investigate the temporal dynamics of brain and cardiac activities in healthy subjects who underwent an emotional elicitation through videos. We demonstrate that, within the first few seconds, emotional stimuli modulate heartbeat activity, which in turn stimulates an emotion intensity (arousal)–specific cortical response. The emotional processing is then sustained by a bidirectional brain–heart interplay, where the perceived arousal level modulates the amplitude of ascending heart-to-b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

7
1

Authors

Journals

citations
Cited by 87 publications
(118 citation statements)
references
References 89 publications
5
111
1
1
Order By: Relevance
“…For instance, the descending interplay to the heart is usually associated to arousal only [6]. However, the analysis of the bidirectional interactions of the brain with peripheral cardiac activity showed that the reported arousal was correlated with ascending modulations from cardiac vagal activity [141]. The hypothesis introduced here is that the physiological and cognitive processes involved in interoception, and subjectivity, would involve a dynamic and cyclic information exchange.…”
Section: Uncovering Brain-heart Interactions Through Physiological Mo...mentioning
confidence: 83%
See 2 more Smart Citations
“…For instance, the descending interplay to the heart is usually associated to arousal only [6]. However, the analysis of the bidirectional interactions of the brain with peripheral cardiac activity showed that the reported arousal was correlated with ascending modulations from cardiac vagal activity [141]. The hypothesis introduced here is that the physiological and cognitive processes involved in interoception, and subjectivity, would involve a dynamic and cyclic information exchange.…”
Section: Uncovering Brain-heart Interactions Through Physiological Mo...mentioning
confidence: 83%
“…Importantly, the changes in sympathetic activity precede the brain network organization, suggesting causal interactions [138]. Sympathovagal modulations towards brain oscillations shape emotional and physical arousal [140,141]. The locus coeruleus in the brainstem, which regulates arousal and autonomic function, also shapes neuronal excitability across the brain [142][143][144], suggesting further links between autonomic activity and the orchestrating of neuronal dynamics during conscious processing.…”
Section: Consciousness and Complexity In The Brain-heart Communicatio...mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it has been shown that the respiratory rate shapes olfactory memory 70,71 , emotions 72 , and reaction time 73 , and coordinates the coupling of brain oscillations during sleep 7476 as well as during wakefulness 7782 . These results indicate that cardiorespiratory activity contribute to the shaping of attention and perception, and relative changes in respiration and heart rates are part of ongoing bidirectional brain-heart interplay processes 83 , similar to emotions or stress 84,85 .…”
Section: Discussionmentioning
confidence: 83%
“…It has been shown that indeed there is an information exchange between the brain and the visceral signals when studying the brain-heart axis as a proxy for sympathovagal-cortical interactions during stress [23]. Though, the stress and emotion arousal effects may diverge in the neurophysiology [21, 24, 25], having a comprehensive regional autonomic system activity response measure with the brain interactions provides an axis that can aid in studying the brain-body interactions during psychological emotional disorders using an all-in-one method.…”
Section: Introductionmentioning
confidence: 99%